Stereotactic body radiotherapy (SBRT) for adrenal metastases of oligometastatic or oligoprogressive tumor patients - König, Laila; Häfner, Matthias; Katayama, Sonja; Körber, Stefan A.; Tonndorf-Martini, Eric; Bernhardt, Denise; Nettelbladt, Bastian von; Weykamp, Fabian; Hoegen-Saßmannshausen, Philipp; Klüter, Sebastian; Susko, Matthew S.; Debus, Jürgen; et al. (Radiation oncology, 2020)
Local ablative treatment strategies are frequently offered to patients diagnosed with oligometastatic disease. Stereotactic body radiotherapy (SBRT), as ablative treatment option, is well established for lung and liver metastases, whereas for isolated adrenal gland metastases the level of evidence is scarce.
Gesehen am 30.03.2020